Combination of Intravitreal Injection of Ranibizumab and Photocoagulation for the Treatment of Aggressive Posterior Retinopathy of Prematurity with Vitreous Hemorrhage - Yu Xu; Xiaoli Kang; Qi Zhang; Qiujing Huang; Jiao Lv; Peiquan Zhao (Journal of Ophthalmology)
To investigate the efficacy of intravitreal ranibizumab (IVR) combined with laser photocoagulation for aggressive posterior retinopathy of prematurity (AP-ROP) patients with vitreous hemorrhage, we conducted a retrospective observational case series study. A total of 37 eyes of 20 patients’ medical records were reviewed. Patients first received IVR (0.25 mg/0.025 mL) and later photocoagulation. The mean postconceptual age of injection was 34.6 ± 1.4 weeks, and the mean follow-up period was 39.3 ± 8.3 weeks. During the follow-up, 96.6% eyes had various degree of rapid absorption of vitreous hemorrhage after IVR. The mean time of received first photocoagulation after IVR was 4.8 ± 2.9 weeks. Ten (27.0%) eyes received second laser therapy and the mean time of second laser therapy after IVR was 3.2 ± 0.8 weeks. All eyes exhibited adequate regression of ROP and were stable with attached retina. Fibrosis membrane was observed in seven eyes (18.9%) and three of them demonstrated mild ectopic macula. No significant side effects related to IVR were observed. So IVR could be conducted as primary treatment of AP-ROP associated with vitreous hemorrhage, which can improve the fundus visibility, followed by conventional photocoagulation. Further randomized controlled trials are necessary to compare the clinical efficacy and safety with conventional interventions.